The determinants of Mexican migrants' duration in the United States: Family composition, psychic costs, and human capital - Shan Li (IZA Journal of Migration, 2016)
This paper analyzes the determinants of migration duration focusing on family composition and human capital. A utility maximization model is built to show that migrants face a trade-off between avoiding psychic costs from leaving family members and accumulating wealth to support their consumption. The empirical analysis on Mexican men's US experience carried out using the hazard model shows that marriage and children, which imply a heavier financial burden, are negatively associated with migrants' duration in the USA. Fathers with more young children under age 12 stay even shorter, because taking care of them is time intensive.
Keywords: F22; O15; J12; 330; Family composition; Psychic costs; Human capital; Cox proportional hazard model